(untitled) (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
Author: Mrs. Parimala Vudikala Assistant Professor, Department of Pharmaceutics, Joginpally BR Pharmacy College, Moinabad, Hyderabad, Telangana, India Abstract: Filtration is a critical separation process in pharmaceutical manufacturing used to remove solid particles from liquids or gases. This operation is essential for purifying raw materials, intermediate products, and final drug formulations. Various filtration mechanisms, including surface straining, depth filtration, and cake filtration, are employed depending on the nature of the suspension and desired level of separation. The selection of appropriate filter media, such as membrane filters, depth filters, or cartridge filters, is crucial for achieving optimal filtration efficiency. Factors influencing filtration performance include particle size distribution, filter pore size, pressure differential, and filtration rate. The principles of constant pressure and constant rate filtration are explored, along with their applications in different pharmaceutical processes. Advanced filtration techniques, such as tangential flow filtration and sterile filtration, are discussed in the context of biotechnology products and aseptic processing. Quality control measures, including integrity testing of sterilizing filters and validation of filtration processes, are essential to ensure product sterility and purity. Understanding filtration principles and practices is vital for maintaining product quality and compliance with regulatory standards in pharmaceutical manufacturing Keywords: Separation, Filter media, Particle retention, Sterile filtration, Cake formation, Process validation View PDF